Predicting halal cosmetics purchase intention among consumers in Johor Darul Takzim - Abd Aziz, Noreen Noor (2021)
Although there is a vast and growing number of literature reviews towards the consumer purchase intention, most of these empirical studies were focused more on the conventional purposes rather than purchase intentions for halal cosmetic products. Thus, the objectives of this research are: (1) to identify the influence of attitude, subjective norm, perceived behavioural control, knowledge, safety, and purity towards the intention to purchase halal cosmetic product among consumers, (2) to examine the moderating role of education level between the selected variables (attitude, subjective norm, and perceived behavioural control) and the intention to purchase halal cosmetic product among consumers, and (3) to propose a framework for halal cosmetic products. In this quantitative research study, a structured questionnaire using a 5-point Likert Scale was used as an instrument for the data collection. A total of 400 questionnaires were distributed to consumers in Johor with a response rate of 99.5%. The data was analysed using Partial Least Squares Model Analysis (PLS-SEM). The findings indicated that attitude, subjective norm, perceived behavioural control, knowledge, and purity were found to be positively associated with, and being an influential predictor of purchase intention of halal cosmetic products. Education level was found to be a significant moderator of association between attitude and purchase intention of halal cosmetic products. This study also provides further insights of potential marketing strategies by halal cosmetic product manufacturers, as well as the prospective halal cosmetic industry in Malaysia as a whole.